2007
DOI: 10.1111/j.1399-3046.2007.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated cord blood transplantation in children with sickle cell disease: Review of four‐center experience

Abstract: UCBT was performed in seven children with SCD and stroke (HLA match 4/6 n=5; 5/6 n=2). Four received myeloablative regimens (BU, CY, ATG plus FLU in one patient). One had primary graft failure, three had sustained engraftment, two with grade III-IV GVHD (one died, one developed chronic GVHD), one with stable mixed chimerism. Three patients treated with reduced-intensity regimens (FLU, BU or CY, ATG, TLI) failed to engraft; one engrafted after second UCBT (HU, TT, RXA, ALZ, TBI). Four patients (57%) developed v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 19 publications
1
51
0
Order By: Relevance
“…Indeed, it has been shown that UCB may not engraft after RIC in chemotherapy-naive patients. [25][26][27] However, it is expected that the patients enrolled in future trials will have received intensive chemotherapy before transplantation. First, this salvage approach is aimed at patients refractory to former chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been shown that UCB may not engraft after RIC in chemotherapy-naive patients. [25][26][27] However, it is expected that the patients enrolled in future trials will have received intensive chemotherapy before transplantation. First, this salvage approach is aimed at patients refractory to former chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that a RIC regimen may lead to UCB engraftment in childhood leukemia, 24 some reports suggest that engraftment may be poor in patients with other diseases. [25][26][27] Only one previous patient with a solid tumor was reported to engraft successfully after RIC regimen and UCBT. 28 The objective of this pilot trial was therefore to examine engraftment after RIC of partially matched UCB in children with relapsed or refractory neuroblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…This study was limited in sample size and indicates that a prospective, multicenter trial with similar treatment guidelines might be more effective and informative. 34 Reduced intensity conditioning regimens Efforts to expand the application of HCT for SCD and thalassemia have been restricted not only by lacking suitable donors, but also by the risk of significant toxicity that accompanies this intensive procedure. 35 A recent review of 175 SCD patients treated by conventional HCT observed complications of GR and disease recurrence in 16 patients (9%) with 17 patients (9%) dying of transplantrelated causes.…”
Section: Indicationsmentioning
confidence: 99%
“…In unrelated CBT, although more feasible for pediatric patients on the basis of the availability of 4/6 HLA-matched cord blood unit, it appears to be associated with a great risk of graft rejection and GVHD. The largest study consisting of seven patients reported one death, an EFS of 43%, five patients developed acute GVHD, and one patient chronic GVHD (Adamkiewicz et al 2007). Moreover, CBT for adults is limited by the necessary total nucleated cell count per kilogram of body weight for engraftment to occur.…”
Section: Hematopoietic Stem Cell Transplantation For Sickle Cell Diseasementioning
confidence: 99%